Enhanced water permeation based on nanoporous multilayer graphene membranes: the role of pore size and density. Issue 45 (7th November 2016) - Kim, Dae Woo; Choi, Junghoon; Kim, Daeok; Jung, Hee-Tae
Abstract : Nanoporous graphene (size: ca. 3 nm, density: ca. 10 15 m −2 ) can be synthesized in bulk by KOH activation of pre-oxidized graphite. Abstract : Bulk scale graphenes containing narrow and dense pores are realized via potassium hydroxide activation of pre-oxidized graphite (size: ca. 3 nm, density: ca. 10 15 m −2 ). A film (20 nm thickness) comprised of this nanoporous graphene displays much enhanced water flux ( ca. 37 L m −2 h −1 bar −1 ) compared to that of conventional graphene oxide membranes (∼6 times), while maintaining the seiving performances of GO laminates with ca. 20% rejection for NaCl and up to 99% rejection for various dyes around 1 nm diameter size. This advantageous property is a result of the fact that in addition to the effect of the interlayer stacking of graphene sheets, nanopores in the graphene generated by using the new method serve as additional channels through which water molecules can diffuse. We believe that the new approach will play a key role in preparing and designing graphene membranes with high flux.